THE FORM OF CRIMINAL-LEGAL REGULATION AS THE BASIS OF LEGALITY OF CRIMINAL LIABILITY - Yu. S. Zharikov (Russian Journal of Economics and Law)
Basing on the analysis of the forms of criminal-legal regulation, the author views the issues of providing and protection of legality of the criminal liability realization. It is proposed to thoroughly distinguish the private (qualitative feature) and general (legally established sequence of realization) factors of criminal liability provision.